2000
DOI: 10.1002/1096-9896(2000)9999:9999<::aid-path679>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Clonal patterns in phaeochromocytomas and MEN-2A adrenal medullary hyperplasias: histological and kinetic correlates

Abstract: The relationship among histological features, cell kinetics, and clonality has not been studied in adrenal medullary hyperplasias (AMHs) and phaeochromocytomas (PCCs). Thirty-four PCCs (23 sporadic and 11 MEN-2A (multiple endocrine neoplasia type 2A)-related tumours, the latter associated with AMH) from females were included in this study. Representative samples were histologically evaluated and microdissected to extract DNA and evaluate the methylation pattern of the androgen receptor alleles. At least two ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 26 publications
0
41
0
Order By: Relevance
“…However, precancerous lesions and early neoplasms (even those with low nuclear grade) can show the genetic and kinetic Kinetic and microsatellites in AMN features of established malignancies (clonal proliferation with accumulation of cooperative genetic abnormalities, and advantageous proliferation/ apoptosis disbalance), along with molecular evidence of progression. 1,6,17,27,28,44,45 This progression would be related to the accumulation of genetic abnormalities and selective segregation of tumor cells with invasive capabilities, which are frequently topographically distributed. 20,23,46 A progressive and significant reduction in marker expression from junctional to deep dermal compartments was a general finding mirrored by the microsatellite profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, precancerous lesions and early neoplasms (even those with low nuclear grade) can show the genetic and kinetic Kinetic and microsatellites in AMN features of established malignancies (clonal proliferation with accumulation of cooperative genetic abnormalities, and advantageous proliferation/ apoptosis disbalance), along with molecular evidence of progression. 1,6,17,27,28,44,45 This progression would be related to the accumulation of genetic abnormalities and selective segregation of tumor cells with invasive capabilities, which are frequently topographically distributed. 20,23,46 A progressive and significant reduction in marker expression from junctional to deep dermal compartments was a general finding mirrored by the microsatellite profile.…”
Section: Discussionmentioning
confidence: 99%
“…7,18,20,24,27,28 This ratio represents 80% of clonal cells in the sample and hence was used to increase the detection specificity. 7 (b) Additional allele bands present in tumor samples but not in the corresponding controls were considered as evidence of somatic microsatellite abnormalities.…”
Section: Tsg Microsatellite Analysismentioning
confidence: 99%
“…Therefore, we determined the intratumoral molecular heterogeneity in a series of 12 benign tumors (11 PCC and 1 sPGL) and 8 malignant tumors (seven PCC and one sPGL) by LOH analysis in different areas of the tumors. Molecular intra-tumoral heterogeneity within tumors has been reported in 55% of meningiomas (Sayagues et al 2004), 45% of renal tumors (Nenning et al 1997), 2.7% of cervical cancer (Bachtiary et al 2006), and in 8.8% of PCC (Diaz-Cano et al 2000). It is important to emphasize that these frequencies show extreme variation because 1) the amount of markers or probes used per study are different.…”
Section: Discussionmentioning
confidence: 99%
“…Jarbo et al (2005) reported that the ratios of chromosome 22q loss in some PCC samples were higher than expected for a single allele ratio, and suggested this could be due to intra-tumoral heterogeneity. Diaz-Cano et al (2000) investigated heterogeneity of sporadic and MEN 2-related PCC and adrenal medullary hyperplasia (AMH) nodules, by determining the methylation patterns of the androgen receptor (AR) gene, localized on the X-chromosome. All informative AMH showed concordant inactivation of the same alleles in different nodules from the same adrenal gland, suggesting that these AMH nodules arose from a common progenitor and are clonally related proliferations.…”
Section: Introductionmentioning
confidence: 99%
“…The sections were mounted on positively charged slides (Superfrost Plus, Fisher Scientific, Fair Lawn, NJ), baked at 60°C for 2 hours, and processed as described [16,17,25]. After routine dewaxing and rehydration, endogenous peroxidase quenching, and antigen heat retrieval (pressure cooker, citrate buffer [10 mmol/L], for all antibodies), the slides were transferred to a moist chamber.…”
Section: Immunohistochemical Detection Of Tp53 Mlh1 and Msh2mentioning
confidence: 99%